Analisis Tingkat Kepuasan Pengunjung Desa Wisata Kembang Kuning di Kabupaten Lombok Timur - JULIANI, SEPTIA; SURYAWARDANI, I GUSTI AYU OKA; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of Visitor Satisfaction Level at Kembang Kuning Tourism Village in East Lombok Regency.  This study aims to 1) analyze the level of visitor interest and destination performance, 2) analyze destination attributes that need to be improved, 3) analyze the level of visitor satisfaction in the Kembang Kuning Tourism Village based on the level of visitor interest and the performance of the Kembang Kuning Tourism Village. The research sample amounted to 95 visitors. Data were analyzed using Important Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The results showed that 1) the level of visitor interest (4.25) was higher than the level of performance (4.08), 2) the attributes of the Kembang Kuning Tourism Village that needed to be improved were described in Quadrant I, namely several indicators on accessibility, amenity, ancillary, price, promotion, process. 3) the CSI value is 81.72%, which indicates that the satisfaction level of visitors to the Kembang Kuning Tourism Village in East Lombok Regency is categorized as very satisfied. This indicates that in general, visitors are very satisfied with the performance of the Kembang Kuning Tourism Village.